Milieu, spirit, flesh and fusion in Le Corbusier’s life and work - Benton, Tim (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2022)
How can a study of Le Corbusier’s post-war work – the Poème de l’angle droit and Modulor 1 and 2 – throw light on his earlier preoccupations. These works are retrospective and confessional. They are obsessed with the question ‘By what right may I create?’ The former work looks for answers in experience and the latter in the ‘divine’ world of mathematics. From at least 1906, when he bought and devoured Edouard Schoré’s Les grands initiés, Le Corbusier had a strong sense of predestination and a conviction that suffering was a necessary part of the voyage to enlightenment. His dualism, the belief in the separation of the spiritual and material worlds, encouraged him to view mathematics as part of the ‘hidden world’ of the spirit. His problem, in the research leading up to Modulor 1, was how to reconcile divine proportion and human experience. He invariably described the passage from the material to the spiritual worlds in terms of physical processes – smoking, simmering, brewing, giving birth. This idea, clearly described in one of his lectures in 1929, and his frequent discussion of ‘cosmic’ forces and symbolism during the 1930s, indicates that these ideas were well entrenched before the war.